Comparative analysis between HEC-RAS models and IBER in the hydraulic assessment of bridges (Gaceta Técnica, 2017)
This work aims to perform a comparative analysis between the Hec-RAS and IBER models, in the hydraulic evaluation of rivers with structures such as bridges. The case of application was the La Guardia creek, located in the road that communicates the cities of Barquisimeto-Quíbor, Venezuela. The first phase of the study consisted in the comparison of the models from the conceptual point of view and the management of both. The second phase focused on the case study, and the comparison of the results obtained from the hydraulic analysis. It was observed that the behavior in both models presented great similarity in the flow profile as in the regime. Upstream of the two bridges predominate the subcritical regime, where the highest depths and the lowest velocities are present. The opposite occurs downstream of the two bridges, where the supercritical regime prevails, high speeds and minimum depths. It is concluded that, for rivers with simple geometry and preferably with a single bridge, the Hec-RAS one-dimensional software is presented as the best alternative of use due to the ease of data entry, providing reliable results in a shorter time. While the IBER package is two-dimensional, it represents a better option for modeling rivers with more irregular geometries, when there is a special interest in the hydraulic behavior of the flow through stirrups and stacks, and having two or more bridges with separation reduced.
Keywords: hydraulic simulation; rivers; bridge; HEC-RAS; IBER